Comparative analysis of complications in patients waith abdominal aortic aneurysm treated with the traditional method and with stent-graft - Ścisło, Lucyna; Domanus, Renata; Walewska, Elżbieta; Puto, Grażyna; Szczepanik, Antoni M.; Pietruszka, Szymon; Brzuszkiewicz, Karolina; Paszko, Agata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Introduction : Comparative analysis of complications in patients with abdominal aortic aneurysm treated with the classic method and the endovascular method with stent-graft implantation. Material and methods:  Eighty patients with abdominal aortic aneurysm (20 operated with classic method and 40 with endovascular – stent-graft implantation) were included. For analysis of medical documentation and statistical techniques, the χ 2 , Shapiro-Wilk, and Kolmogorov-Smirnov tests were used. Results : Differences in postoperative complications occurrence were observed: in the traditional method compared with endovascular method: in terms of the respiratory system 30% vs. 5%, digestive system 27.5% vs. 32.5%, urinary system 22.5% vs. 17.5%, circulatory system 15% vs. 20%, and wounds 12.5% vs. 50%. The data concerning the dependence between complications and traditional surgery (p = 0.0001) and between complications and the stent-graft method (p = 0.00001) showed differences in the number of complications (p = 0.00001). In terms of the dependence between complications and coexisting illness occurrence p = 0.060 was set as the level of significance. In the method with stent-graft the level of significance was p = 0.060. Conclusions : Patients operated with the method employing stent-graft implication had fewer complications, most of which occurred in terms of wounds, compared with patients operated with the classic method, who experienced respiratory system complications more often and wound complications most seldom. Statistical dependence between the number of complications and coexisting illness occurrence were not detected.